Family physician service quality and sustainability: a roadmap for Pakistan’s healthcare sector - Saifullah,; Ma, Zhiqiang; Li, Mingxing; Maqbool, Muhammad Qasim; Chen, Feng (Frontiers in Medicine, 2024)
Introduction The number of family medicine consultants has increased during and after the COVID-19 pandemic. However, research on family medicine services specific to Pakistan remains limited. Therefore, this study aimed to explore family physician services in Pakistan. Methods To meet the study goals, we collected data using snowball and purposive sampling. A questionnaire was used exclusively to collect data from family physician consultations. The data were examined using the SmartPLS structural equation model to test the study model’s reliability and validity. Results The study findings showed that using resource utilization and allocation, utilization of technology, professionalism improvement, medical attention, cooperation, and caring were positively significant to employee welfare and assistance in family medicine services. These dimensions were also positively significant to community involvement and advocacy for the sustainable development of family medical services in Pakistan. Conclusion The study concluded that effective resource utilization, professionalism, medical care, cooperation, and the evaluation of quality and outcomes are key factors in promoting the growth of family medicine services. These indicators may enhance staff satisfaction, community involvement, and family physician service sustainability.